Tes Kemampuan Bahasa Inggris Berbasis Komputer untuk Seleksi Beasiswa: Tantangan, Strategi, dan Implementasi pada Kementerian Keuangan - Muhammad Yoga Prabowo; Sarah Rahmadian (Fakultas Seni Rupa dan Desain ITB, 2022)
The need for a safe and versatile testing system during COVID-19 pandemic for scholarship selection prompted the Financial Education and Training Agency (FETA), an echelon-1 unit under the Ministry of Finance, to design the Aplikasi Ujian Online computer-based test platform. This paper focused on exploring challenges in developing and administering English competency assessment through the computer-based platform and the strategies to overcome them. The research used the descriptive method with direct observation and questionnaire for data collection. Three receptive skills (listening, structure, and reading comprehension) were measured on 337 applicants of the Ministerial Scholarship offered by the Ministry of Finance in 2021. A post-test questionnaire was administered to investigate test takers' perceptions. The findings showed that loading time and login difficulty were the most common issues. However, preformulated risk-mitigation strategies were found to be effective in resolving the issues. Overall, the questionnaire result showed a significantly positive perception of the computer-based English competency test.